2021
DOI: 10.1016/j.ijid.2021.08.057
|View full text |Cite
|
Sign up to set email alerts
|

HIV viral load suppression following intensive adherence counseling among people living with HIV on treatment at military-managed health facilities in Uganda

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This was comparable to other studies. [32][33][34][35] Poor adherence to HAART has been highly linked to the development of drug resistance among PLHIV, [36][37][38][39] and this drug resistance leads to virological non-suppression as HIV replication is not well suppressed, which, in turn, leads to an increase in the viral load. [40][41][42] This shows the importance of continuous adherence monitoring and counseling among PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to other studies. [32][33][34][35] Poor adherence to HAART has been highly linked to the development of drug resistance among PLHIV, [36][37][38][39] and this drug resistance leads to virological non-suppression as HIV replication is not well suppressed, which, in turn, leads to an increase in the viral load. [40][41][42] This shows the importance of continuous adherence monitoring and counseling among PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding remains consistent with numerous other studies that have shown a low effectiveness of IAC in causing viral re-suppression among non-suppressed people living with HIV. For instance, a Ugandan study found that only 23% of paediatric patients with HIV achieved viral suppression after IAC [46]; another Ugandan study evaluated the outcomes of IAC in improving viral suppression and found that 48.2% of participants with HIV achieved viral suppression following IAC [47]; and in Zimbabwe, 31.2% of participants with HIV who underwent a repeat VL after IAC achieved VL suppression [48]. This low success rate of IAC could be due to various challenges affecting the implementation of IAC, including clients missing IAC sessions, shortage of food, stigma and discrimination, delayed VL results, a lack of incentives, and heavy workloads, among others [46,49].…”
Section: Discussionmentioning
confidence: 99%
“…Like elsewhere [ 22 , 23 ], studies have been conducted in Uganda to assess implementation of IAC from the lens of the health care providers (family and health workers) [ 11 , 24 , 25 ], and PLHIV [ 26 , 27 ]. In this study we focused on the healthcare providers and explored the barriers to the utilization of the UMOH IAC framework in order to identify potential solutions that may be more broadly applicable and feasible [ 19 ].…”
Section: Discussionmentioning
confidence: 99%